Compulsory Secondary Education explained to parents. (Journal of Parents and Teachers, 2025)
The article discusses the changes occurring in education due to the reform, where parents begin to familiarize themselves with Compulsory Secondary Education (ESO) and leave behind the previous General Basic Education (EGB). During these four years, students will continue to develop thinking skills, and the content will be distributed throughout the years, with procedures and concepts being consistently present.
Keywords: ESO; Reforms; education; parents